New logarithmic operational laws and their applications to multiattribute decision making for single-valued neutrosophic numbers. (December 2018) - Garg, Harish; Nancy
Abstract: Neutrosophic set, initiated by Smarandache, is a novel tool to deal with vagueness considering the truth, indeterminacy and falsity memberships satisfying the condition that their sum is less than 3. This set can be used to characterize the information more accurately than the intuitionistic fuzzy set. Under this set, the objective of this manuscript is to present some new operational laws called as logarithm operational laws with real number base λ for the single-valued neutrosophic (SVN) numbers. Various desirable properties of the proposed operational laws are contemplated. Further, based on these laws, different weighted averaging and geometric aggregation operators are developed. The properties such as idempotency, monotonicity, boundedness are provided to support the proposed operators. Then, we utilized these operations and operators to present a multiattribute decision making method to solve the decision-making problems. A real numerical example is given to demonstrate the approach under SVN environment. The legitimacy of the proposed strategy is exhibited with a numerical illustration and compared the results with the several existing approaches result.